Surgical Aspects of Split Liver Transplantation: а Review - S. V. Gautier; R. A. Latypov; A. R. Monakhov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. To analyse the surgical aspects of performing a split liver transplantation in patients with end-stage liver disease.Key findings. Split liver transplantation (SLT) is a technique allowing two functional grafts to be obtained from one deceased donor to simultaneously save the lives of two recipients. The global clinical experience of SLT application currently comprises more than three decades. Criteria necessary for successful SLT were developed, based both on assessment of graft quality (age and anthropometric characteristics of the donor, laboratory parameters, ultrasound data, length of stay in intensive care, as well as macroscopic intraoperative assessment of the liver), and on the selection of recipients (primarily in accordance with the height-weight characteristics and the use of the GRWR [graftto-recipient weight ratio]). The use of these criteria allows the results to be achieved comparable to other types of liver transplantation (a whole liver from a deceased donor or liver fragments of an intravital donor). However, issues involved with of the optimal choice of surgical techniques remain to be solved, which include such key aspects as the anatomical method of separation (left lateral section and extended right lobe; anatomical left and right lobes of the liver), an optimal method of separation (ex situ or in situ) and others. The issues of logistics of the SLT application, including the principles of allocation of transplants, also remain significant. Ethical aspects are equally important, since, theoretically, the widespread introduction of the SLT technique may increase the risk of graft loss. The immediate and long-term SLT results require further study, which makes it possible to form a more objective opinion on the effectiveness of the technique.Conclusion. SLT shows good results both in the near and in the remote period. The key aspects of SLT performing are a deep understanding of the variant anatomy of the liver and a high level of knowledge of liver resection surgery. The active use of SLT allows the pool of donor organs to be increased, which is of great importance under the conditions of their permanent lack.